Factors and barriers that influence the matriculation of underrepresented students in medicine - Tello, Cynthia; Goode, Christine A. (Frontiers in Psychology, 2023)
Despite many initiatives over more than 4 decades, the diversity of US physicians still does not reflect the diversity of the US population. The present study undertakes a literature review of the last 30 years to investigate barriers and protective factors underrepresented college students encounter as applicants for medical school. Known barriers that influence matriculation into medical school were analyzed such as academic metrics and test scores. Additionally, elements that are less well studied were investigated such as factors perceived as barriers by underrepresented applicants in addition to protective factors that allow them to persist in their journey in the face of difficulties and adversity.